Deactivating economic motives in green consumption through social and moral salience. Issue 3 (13th January 2020) - Johansson, Lars-Olof; Barbopoulos, Isak; Olsson, Lars E.
Abstract : Purpose: This paper aims to examine how social and moral salience influences the activation/deactivation of consumer motives and how this in turn affects costly pro-environmental consumer behavior. Design/methodology/approach: In two experiments involving real purchases, it was tested whether social salience (private vs public choice) and moral salience (recall of neutral vs immoral action) lead to the activation of normative motives, and/or the deactivation of economic motives, and whether this facilitated the purchase of a costlier green product. Findings: Participants were motivated by both economic and normative motives, and they actively made trade-offs between these motives as the choice environment changed. Green consumption was positively influenced by social and moral salience but only when both salience conditions were present simultaneously. However, salience did not lead to the activation of normative motives, as was expected, but to a deactivation of the motive to save money. This may suggest that while the importance of norms was not altered by salience, the perceived value of the green option likely changed in such a way that participants became more inclined to choose the costlier green option. Originality/value: The present research sheds light on how and why social and moral salience influences green consumption. It was demonstrated that social and moral salience influences the tendency to purchase costlier green products, however, only when both are combined. Also, the effects of social and moral salience may not rely on the activation of facilitating social and moral motives but rather on the deactivation of conflicting economic motives.